Monolith Dental Bridge by Soft Machining of Dried Ceramic Dough - Seesala, Venkata Sundeep; Vaidya, Pravin Vasudeo; Rajasekharan, Ragavi; Kumar Ojha, Atul; Jana, Subhodeep; Pal, Barnali; Dhara, Santanu (Frontiers in Dental Medicine, 2021)
All ceramic fixed restorations are gaining popularity due to increased aesthetic consciousness in the younger population. Monolith ceramic crowns and bridges are preferred to withstand the masticatory loads where availability of occlusal height is limited. Machining green blanks of ceramic with organic binders has been studied to reduce the loss of final strength, cost and wastage associated with milling partial sintered and sintered blanks. Notches on the surface/edge associated with green milling will disappear after sintering in contrast to sintered state machining where, diamond polishing is essential. Herein, we explored a novel ceramic dough process to form a green body of alumina or 3Mol%YSZ and CNC machining was performed on dried dough. MicroCT analysis of the bridges after sintering, revealed a negligible defect volume, 0.06-0.08% of the total volume with randomly dispersed voids. Precision analysis of the sintered bridges with respect to reference file resulted in deviation range of +0.56 to -0.79 mm, with negligible deviation on the cementation surface. The green machined surface had a roughness profile of 1.2-1.7 µm after machining and 2.2-2.4 µm after sintering as revealed by 3D profilometry.